Synthesis of Pluraflavin A “Aglycone” - Wright, Benjamin J.D. (2008)
The “aglycone” of pluraflavin A (2) has been synthesized. The key features of this synthesis include a 1,3-dipolar cycloaddition between a nitrile oxide (cf. 14) and an olefin (22) to yield an isoxazoline followed by subsequent conversion into the γ-pyrone of pluraflavin A. The epoxide moiety linked to the pyrone is installed prior to Diels-Alder installation of the D-ring, which allows access to a number of potentially active cytotoxic intermediates en route to the final compound. The preliminary in vitro results of two such compounds are also included with the racemic title compound exhibiting cytotoxicity in the nanomolar range.